Asia Oceania Guidelines for the Implementation of Programs for Cervical Cancer Prevention and Control. (14th February 2011) - Ngan, Hextan Y. S.; Garland, Suzanne M.; Bhatla, Neerja; Pagliusi, Sonia R.; Chan, Karen K. L.; Cheung, Annie N. Y.; Chu, Tang-Yuan; Domingo, Efren J.; Qiao, You Lin; Park, Jong Sup; Tay, Eng Hseon; Supakarapongkul, Wisit
Abstract : This paper aims to provide evidence-based recommendations for health professionals, to develop a comprehensive cervical cancer program for a clinic, a community, or a country. Ensuring access to healthcare is the responsibility of all societies, and the Asia Oceania Research Organisation in Genital Infections and Neoplasia (AOGIN) is committed to working collaboratively with governments and health professionals to facilitate prevention programs, to protect girls and women from cervical cancer, a disease that globally affects 500, 000 and kills nearly 300, 000 women annually, just over half of whom are in the Asia Oceania region. We share the vision that a comprehensive program of vaccination, screening, and treatment should be made accessible to all girls and women in the world. The primary purpose of these guidelines is to provide information on scientific evidence on the different modalities and approaches of cervical cancer prevention programs, for high resource and low resource settings. The secondary purpose is to provide an overview of the current situation of cervical cancer control and prevention in various Asian Oceania countries: their views of an ideal program, identified obstacles, and suggestions to overcome them are discussed.